The Use of Endo-Cellulase and Endo-Xylanase for the Extraction of Apple Pectins as Factors Modifying Their Anticancer Properties and Affecting Their Synergy with the Active Form of Irinotecan - Jerzy Maksymowicz; Anna Palko-Łabuz; Beata Sobieszczańska; Mateusz Chmielarz; Mirosława Ferens-Sieczkowska; Magdalena Skonieczna; Agnieszka Wikiera; Olga Wesołowska; Kamila Środa-Pomianek (MDPI AG, 2022)
Pectin constitutes an essential component of dietary fiber. Modified pectins from various sources possess potent anticancer and immunomodulatory activities. In this study, two pectins isolated from apple pomace by Trichoderma enzyme treatment, PX (with endo-xylanase) and PCX (with both endo-cellulase and endo-xylanase), were studied in colon cancer cell lines (HCT 116, Caco-2, and HT-29). Both pectins reduced colon cancer cell viability, induced apoptosis, and increased intracellular amounts of reactive oxygen species. Additionally, synergy between pectin and an active form of irinotecan, SN-38, in all aspects mentioned above, was discovered. This drug is a common component of cytotoxic combinations recommended as treatment for colon cancer patients. PX and PCX demonstrated significant anti-inflammatory activity in lipopolysaccharide-stimulated cells. Interaction of apple pectins with galectin-3 and Toll-like Receptor 4 (TLR4) was suggested to be responsible for their anticancer and anti-inflammatory effect. Since PCX was more active than PX in almost all experiments, the role of the enzyme used to obtain the pectin for its biological activity was discussed. It was concluded that co-operation between both enzymes was needed to obtain the molecule of the most beneficial properties. The low molecular mass of PCX together with a high proportion of rhamnogalacturonan I (RG I) regions seemed to be crucial for its superior activity.